Pax5 (BSAP) regulates the murine immunoglobulin 3' alpha enhancer by suppressing binding of NF-alpha P, a protein that controls heavy chain transcription. - Neurath, M F (1995)
The Pax5 transcription factor BSAP (B-cell-specific activator protein) is known to bind to and repress the activity of the immunoglobulin heavy chain 3' alpha enhancer. We have detected an element--designated alpha P--that lies approximately 50 bp downstream of the BSAP binding site 1 and is required for maximal enhancer activity. In vitro binding experiments suggest that the 40-kDa protein that binds to this element (NF-alpha P) is a member of the Ets family present in both B-cell and plasma-cell nuclei. However, in vivo footprint analysis suggests that the alpha P site is occupied only in plasma cells, whereas the BSAP site is occupied in B cells but not in plasma cells. When Pax5 binding to the enhancer in B cells was blocked in vivo by transfection with a triple-helix-forming oligonucleotide an alpha P footprint appeared and endogenous immunoglobulin heavy chain transcripts increased. The triple-helix-forming oligonucleotide also increased enhancer activity of a transfected construct in B cells, but only when the alpha P site was intact. Pax5 thus regulates the 3' alpha enhancer and immunoglobulin gene transcription by blocking activation by NF-alpha P.